Effect of trench structure on reverse characteristics of 4H-SiC junction barrier Schottky diodes. (15th November 2017) - Konishi, Kumiko; Kameshiro, Norifumi; Yokoyama, Natsuki; Shima, Akio; Shimamoto, Yasuhiro
Abstract: We investigated 4H-SiC trench junction barrier Schottky (JBS) diodes from the viewpoints of the tradeoff between the electric field at the Schottky contact interface ( E s ) and the forward voltage drop, the effect on reduction of reverse leakage current, and the device yield. By calculating E s, we found that the trench JBS structure can make E s one order of magnitude smaller than that of the planar JBS structure, when the bevel angle (θ) is set between 80 and 90°. Moreover, 600 V/50 A trench JBS diodes were fabricated, and their reverse leakage current at 600 V was made 10 2 times smaller than that of the planar JBS diode by effectively reducing E s . We also found that this reduction in reverse leakage current decreases the number of low breakdown voltage samples below 600 V and improves the yield.